Diseño de un ladrillo de arcilla de bajo peso incluyendo roca volcánica y tierras diatomeas - Víctor Hugo, Pulgar Naranjo (2019)
The construction industry is one of the most relevant sources of economy in our country. Since, it moves large-scale economic and human resources. For the construction of buildings in civil works, light and high strength materials had needed; therefore, the present research aims to design a low-weight clay brick including volcanic rocks and diatomaceous earth, which has good resistance, with improved performance fulfilling with norms and quality standards. For this reason, bricks were made with different dosages using three types of materials such as diatomaceous earth, Chimborazo and Tungurahua volcanic rocks. Using the optimization procedure of mixtures was possible to know that the dosage of Chambo diatomaceous earth and clay in a 70/30 ratio respectively with disks of (2 x 7.5) cm, an optimization factor of 9.71 MPa / kg and a compression test resistance of 11.24 MPa and a reduction of 53% of weight related to artisan bricks. In the case of the dosage of volcanic rock and Chambo clay in a 40/60 ratio in disks of (2x7.5) cm, an optimization factor (f opt) of 5.22 MPa / kg and a resistance to the compression test are obtained of 5.76 Mpa and a reduction in weight of 4% related to artisan bricks. The result indicates that bricks with Chambo diatomaceous earth and clay carry out with the regulations while those made with volcanic rock were eliminated. The design of this new brick will be useful for the construction of homes and buildings with a considerable reduction in dead load and at a lower cost providing an economic and innovative solution for the construction industry.